Personal 3D Audio System with Loudspeakers - Song, Myung-Suk; Zhang, Cha; Florencio, Dinei; Kang, Hong-Goo (ICME (Hot3D), 2010)
Traditional 3D audio systems often have a limited sweet spot for the user to perceive 3D effects successfully. In this paper, we present a personal 3D audio system with loudspeakers that has unlimited sweet spots. The idea is to have a camera track the user’s head movement, and recompute the crosstalk canceller filters accordingly. As far as the authors are aware of, our system is the first non-intrusive 3D audio system that adapts to both the head position and orientation with six degrees of freedom. The effectiveness of the proposed system is demonstrated with subjective listening tests comparing our system against traditional non-adaptive systems.